2001
DOI: 10.1046/j.1365-2516.2001.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental health indices and caries‐related microflora in children with severe haemophilia

Abstract: The purpose of this work was to investigate the prevalence of dental caries, bacterial dental plaque, gingivitis, enamel defects and caries- related microflora in children with severe haemophilia. Thirty-eight children with severe haemophilia (factor VIII and IX < 2 U dL(-1)) were recruited from Great Ormond Street Hospital for Children and matched for age, gender and ethnicity with healthy control children from the Eastman Dental Institute. Indices were recorded for decayed, missing, and filled teeth and surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
58
2
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 19 publications
11
58
2
7
Order By: Relevance
“…There is no consensus among the investigators with regard to dental and oral health, as well as to quality of life of CBD patients. Results similar to those of the present study have been reported in studies from England, Ireland, Germany and Egypt [17][18][19][20]; however, a poorer dental situation in CBD patients compared with controls is found in Poland, Turkey and India [20][21][22][23]. Inconsistency in the level of provided health care in different communities is probably the main causative factor.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There is no consensus among the investigators with regard to dental and oral health, as well as to quality of life of CBD patients. Results similar to those of the present study have been reported in studies from England, Ireland, Germany and Egypt [17][18][19][20]; however, a poorer dental situation in CBD patients compared with controls is found in Poland, Turkey and India [20][21][22][23]. Inconsistency in the level of provided health care in different communities is probably the main causative factor.…”
Section: Discussionsupporting
confidence: 89%
“…A number of studies reported lower oral hygiene/plaque scores among CBD, although their gingival situation was similar. [17,20,22,24] The present study also investigated the impact of dental and oral health on aspects of oral health-related quality of life such as laughing, eating, emotional and social wellbeing. We could not find clear differences between CBD and controls in their OHR-QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Remiantis šiais rezultatais galima daryti išvadą, kad HSV tėvai ar globė-jai buvo informuoti apie specialius savo vaikų poreikius, burnos ligų profilaktiką ir geriau prižiū-rėjo savo vaikų dantis. Gautus rezultatus palyginome su kitose šalyse atliktais tyrimais ir galime teigti, kad mūsų gauti duomenys sutapo su tyrimų, atliktų Didžiojoje Britanijoje ir Šiau-rės Airijoje, rezultatais [12,13]. Tai leidžia daryti prielaidą, kad Lietuvos HSV dantų būklė yra panašesnė į anglų ir airių negu į HSV iš tolimesnių ir mažiau išsivysčiusių šalių [14,15].…”
Section: Rezultatų Aptarimasunclassified
“…Ištyrus Šiaurės Airijos ir Didžiosios Britanijos HSV pieninio ir nuolatinio są-kandžio dantų ėduonies paplitimą, rezultatai parodė, kad hemofilijos grupėje dantų ėduonies intensyvumo indeksas KPI/kp buvo mažesnis negu kontrolinėje grupėje [12,13]. Priešingus rezultatus paskelbė Pakistano ir Egipto mokslininkai: HSV turėjo daugiau ėduonies pažeistų, plombuotų ir išrautų dantų, palyginti su kontroline grupe [14,15].…”
unclassified
See 1 more Smart Citation